Overview of Knowledge of Using PPE to Support Safety of Workers at CV. Duta Makmur Abadi - Ulfatun, Ulfatun Nadiyah Putri; Sahri, Moch; Wardana, Juwono; Raja’I, Juwono Muh Yasir (Lembaga Dongan Dosen, 2023)
Therefore, socialization aims to reduce the number of work accidents and work-related diseases in CV. Duta Makmur Abadi is engaged in making AC grille molds, by providing education to workers to pay more attention to health and safety when working, especially in the use of PPE. The methods applied in this socialization activity are conducting field observations and identifying dangerous factors in each production process, interviews through direct question and answer with workers, literature studies, and education in the form of posters with the theme